Visual Metafunctions of Drone Videography in the Presidential Secretariat’s YouTube Public Communication: A Social Semiotic Analysis - Eko Agung Sugiyarto; Marlinda Irwanti Poernomo (PT Agung Media Publisher, 2026)
This study examines how drone videography constructs visual meaning in government public communication through a social semiotic perspective. While drone technology has become increasingly prevalent in governmental media production, existing studies have largely emphasized its technical and aesthetic advantages rather than its role in generating communicative meaning. Addressing this gap, the study analyzes drone videography featured in the Presidential Secretariat's official YouTube channel using the visual social semiotic framework developed by Kress and van Leeuwen. A qualitative approach was employed by examining visual data through three metafunctions namely representational meaning, interactive meaning, and compositional meaning. The analysis focuses on how aerial camera movements, framing, viewing angles, distance, salience, and information value collectively construct relationships between political actors, national space, and audiences. The findings indicate that representational meanings portray the President as an active national leader while simultaneously depicting Indonesia's territorial landscape, infrastructure development, cultural diversity, and strategic national events. Interactive meanings are established through elevated viewing angles, long shots, and dynamic aerial movements that position viewers as observers of state achievements while fostering credibility, authority, and national pride. Compositional meanings are created through the integration of visual salience, spatial organization, and cinematic sequencing, producing coherent narratives that reinforce government legitimacy and national identity.